2015
DOI: 10.1186/1475-2891-14-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and colorectal cancer: results from a Canadian population-based study

Abstract: BackgroundThe relationship between major dietary patterns and colorectal cancer (CRC) in other populations largely remains consistent across studies. The objective of the present study is to assess if dietary patterns are associated with the risk of CRC in the population of Newfoundland and Labrador (NL).MethodsData from a population based case–control study in the province of NL were analyzed, including 506 CRC patients (306 men and 200 women) and 673 controls (400 men and 273 women), aged 20–74 years. Dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 40 publications
5
53
0
1
Order By: Relevance
“…The dietary patterns derived from this data resembled those from previous studies which used similar factor analytic approach (Chen et al, 2015;Keding et al, 2011). What we labeled as a western dietary pattern was similar to two dietary patterns found in the breast cancer study in the northern Tanzania.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The dietary patterns derived from this data resembled those from previous studies which used similar factor analytic approach (Chen et al, 2015;Keding et al, 2011). What we labeled as a western dietary pattern was similar to two dietary patterns found in the breast cancer study in the northern Tanzania.…”
Section: Discussionsupporting
confidence: 79%
“…Confirmation of sampling adequacy of the food group variables was confirmed using the Kaiser-Meyer-Olkin measure with the resultant value of 0.752. As per a study by Chen et al (2015), food groups with factor loadings between -0.4 and 0.4 were disregarded for defining the dietary patterns (Chen, 2015). Principal component factor analysis was used to identify dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified dietary patterns to investigate the association of the total diet on CRC risk. While the study designs, methods, participant populations, and derived dietary patterns differ, the three reviews [33][34][35], three case-control [36][37], and two prospective cohort studies [38][39][40] all concluded that meat-based diets are associated with an increased risk of CRC and that plant-based diets, rich in fruit, vegetables, and low in red and processed meat, may reduce CRC risk. These findings are consistent with Tantamango-Bartley et al [41] who found that vegetarian versus non-vegetarian dietary patterns were associated with significantly reduced cancer incidence (HR 0.92, 95% CI 0.85-0.99).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 5, few papers in humans (with controversial results) have been published on the relationship between unfermented grape derivatives and prevalence of cancer, apart from epidemiological studies showing a protective property of a diet rich in fruits and vegetables [43].…”
Section: Cancermentioning
confidence: 99%